Historical and social considerations of strength training for female athletes - Shurley, J.; Felkar, V.; Greviskes, L.; Todd, J. (Strength and Conditioning Journal, 2020)
Female athletes may be hesitant to fully engage in the weight room. Common concerns include violating social norms through their muscularity, or a lack of competence in strength training. These concerns are rooted in historical efforts to constrain the intensity of female competition and traditional societal assumptions about the attributes of femininity. This work seeks to help strength coaches understand the historical and social background of female concerns about strength training and provides a psychological framework that may be useful in helping female athletes overcome their trepidation about the weight room.